IMPLICATIONS OF BUTYLATED HYDROXYTOLUENE AND OPTIMIZED Piper nigrum EXTRACTS APPLICATION ON QUALITY OF STORED PORK - Adeola Adegoke; Kehinde Sanwo; Silas Hunge; Samuel Olakayode; Oluwafunmilayo Oyelude (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis)
Implications of butylated hydroxytoluene (BHT) and optimized Piper nigrum (White and Black Pepper) aqueous extracts (WPAE and BPAE) incorporation on fatty acid profile and physico-chemical indices of pork subjected to refrigeration storage was investigated. To produce optimized Piper nigrum aqueous extracts, desirability values of WPAE and BPAE were upscaled from 60 and 62% to 71 and 97% respectively using Design Expert12, resulting in the yield of 65 and 87 bio-compounds. Fresh pork (100 g) was apportioned to four treatment groups (each replicated four times), comprising the Control (0% antioxidant); BHT (100 mg of BHT); BPAE (100 ml of BPE) and WPAE (100 ml of WPE), then soaked for 30 min prior to refrigeration storage [day (d) 0, 5 and 10] in a completely randomized design. All parameters examined were influenced (p < 0.05) except additive effect on pork pH. Pork preserved with BPAE and WPAE minimized deterioration of fatty acids (FA) such as oleic, palmitoleic, total mono unsaturated fatty acid (MUFA) and poly unsaturated fatty acid (PUFA) than 0% antioxidant. BPAE had the highest MUFA: SFA, and alongside BHT, had significantly (p < 0.05) low index of atherogenicity. BPAE and WPAE had lesser cooking loss percentages than the Control. Additives X Storage day's effect reveal BPAE yielded least refrigeration loss (%) among samples evaluated and had extensive protective benefits. BPAE had the lowest milligram malondialdehyde per gram tissue on d 10 of storage. Extract from BP may potentially contain compounds that could offer enhanced meat preservation and promote consumer health.